(untitled) - Arlov, Pamela (Upper Saddle River, N.J., 2004)
Clearly organized, highly flexible and refreshingly fun to use, this complete guide to composition and grammar instills in learners a sense of the structure of an essay and the purpose of its various parts—a mental template that will serve them in any type of academic writing and that, once mastered, will give them the freedom to actually enjoy and appreciate the act of writing itself. KEY TOPICS It addresses all parts of the classic five-paragraph essay—thesis, introduction, body and conclusion—in separate, concentrated sections, and includes an abundance of examples and practice exercises to help hone each element. It also contains a separate grammar section and a selection of fifteen readings—complete with reading comprehension questions and writing assignments—to help users take advantage of the strong connection between reading and writing. For individuals who want to improve their written communication skills.
Keywords: English language,English language,College readers,Report writing,Tiếng Anh; Rhetoric,Grammar,Tu từ học